Fast pouch emptying, delayed small intestinal transit, and exaggerated gut hormone responses after Roux‐en‐Y gastric bypass. Issue 4 (29th January 2013) - Dirksen, C.; Damgaard, M.; Bojsen‐Møller, K. N.; Jørgensen, N. B.; Kielgast, U.; Jacobsen, S. H.; Naver, L. S.; Worm, D.; Holst, J. J.; Madsbad, S.; Hansen, D. L.; Madsen, J. L.
Abstract Background Roux‐en‐Y gastric bypass (RYGB) causes extensive changes in gastrointestinal anatomy and leads to reduced appetite and large weight loss, which partly is due to an exaggerated release of anorexigenic gut hormones. Methods To examine whether the altered passage of foods through the gastrointestinal tract after RYGB could be responsible for the changes in gut hormone release, we studied gastrointestinal motility with a scintigraphic technique as well as the secretion of the gut hormones glucagon‐like peptide (GLP)‐1 and peptide YY3‐36 (PYY3‐36) in 17 patients>1 year after RYGB and in nine healthy control subjects. Key Results At meal completion, a smaller fraction of liquid and solid radiolabeled marker was retained in the pouch of RYGB patients than in the stomach of control subjects (P = 0.002 and P < 0.001, respectively). Accordingly, pouch emptying in patients was faster than gastric emptying in control subjects (P < 0.001 and P = 0.004, respectively liquid and solid markers). For the solid marker, small intestinal transit was slower in patients than control subjects (P = 0.034). Colonic transit rate did not differ between the groups. GLP‐1 and PYY3‐36 secretion was increased in patients compared to control subjects and fast pouch emptying of the liquid marker was associated with high gut hormone secretion. Conclusions & Inferences After RYGB, the bulk of foods pass without hindrance into the small intestine, while the small intestinal transit is prolonged. The rapid exposure of the gut epithelium contributes to the exaggerated release of GLP‐1 and PYY3‐36 after RYGB.